2018
DOI: 10.1021/acsami.8b13421
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Delivery from Porous Poly(lactide-co-glycolide) Scaffolds Promotes an Anti-Inflammatory Environment within Visceral Adipose Tissue

Abstract: As biomaterial therapies emerge to address adipose tissue dysfunction that underlies metabolic disease, the immune response to these systems must be established. As a potential therapy, we are investigating resveratrol delivery from porous poly(lactide-co-glycolide) scaffolds designed to integrate with adipose tissue. Resveratrol was selected for its ability to protect mice and primates from high fat diet and broad anti-inflammatory properties. Herein, we report fabrication of scaffolds with high resveratrol l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 83 publications
3
18
0
Order By: Relevance
“…This is because resveratrol is a natural anti-inflammatory and anti-oxidant polyphenol and it has been proven to have the function of relieving abnormal blood picture of AA in the early stage [2]. Its effect of treating chronic anemia was reported to be related to inhibition of IL-1, IL-6 and TNF-α, which was consistent with our results [30, 31]. However, what is the mechanism under the action of resveratrol on blood cells, whether it can affect the proliferation, apoptosis, differentiation and signal transduction of immune cells needed to be confirmed.…”
Section: Discussionsupporting
confidence: 89%
“…This is because resveratrol is a natural anti-inflammatory and anti-oxidant polyphenol and it has been proven to have the function of relieving abnormal blood picture of AA in the early stage [2]. Its effect of treating chronic anemia was reported to be related to inhibition of IL-1, IL-6 and TNF-α, which was consistent with our results [30, 31]. However, what is the mechanism under the action of resveratrol on blood cells, whether it can affect the proliferation, apoptosis, differentiation and signal transduction of immune cells needed to be confirmed.…”
Section: Discussionsupporting
confidence: 89%
“…Scaffolds were fabricated from PLG microparticles using a gas foaming, particulate leaching technique. Particles containing resveratrol (Sigma) were fabricated as previously described 38 . Briefly, a 1:3 volume ratio of dichloromethane (Sigma) and ethanol (Sigma) containing 6% wt/wt PLG (75:25 mol ratio lactide to glycolide 0.76 dl/g, Evonik) and 10 mg/ml resveratrol was added to an aqueous solution of 1% wt/vol PVA (Sigma) in a 1:7 volume ratio and homogenized.…”
Section: Methodsmentioning
confidence: 99%
“…A porous poly (lactide-co-glycolide) scaffold was loaded with anti-inflammatory drug resveratrol to decrease activated monocyte and lymphocyte numbers and increase anti-inflammatory expression cytokines in dysfunctional adipose tissue. It was shown that poly(lactide-co-glycolide) scaffold designed to integrate with adipose tissue could reduce the inflammatory tissue response at the implant site, adjunctive resveratrol administration augmented this anti-inflammatory environment, suggesting an important role of biomaterial in immunomodulation [ 162 ]. The anti-inflammatory drug resveratrol also exerts a protective effect on obesity-induced OA by inhibiting TLR4 via the activation of PI3K/Akt signalling pathways in animal models [ 163 ].…”
Section: Prospects In Obesity-induced Oa Treatmentmentioning
confidence: 99%